IMPLEMENTASI NAN SIGAB DI NAGARI KATAPING KECAMATAN BATANG ANAI KABUPATEN PADANG PARIAMAN - Muhammad Tarmizi; Arie Zella Putra Ulni; Momon Dt. Tanamir (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to analyze and describe 1) the requirements that nagari must have in forming a disaster preparedness nagari in nagari kataping. 2) the process of establishing disaster preparedness villages in Kataping villages. 3) the effectiveness of nagari disaster response readiness on disaster response readiness in nagari kataping. The type of research used is qualitative research. Research informants include the Head of the Prevention and Preparedness Division of BPBD Padang Pariaman Regency, the Wali of Nagari Kataping and the Head of the Nagari Kataping Disaster Preparedness Group (KSB). Research informants were determined using Snowball Sampling, which is a technique for sampling data sources that initially were small in number, but gradually became larger as the research progressed and the need to deepen the information needed to complete the required data. This research can be concluded that 1) the requirements that nagari must have in forming a disaster response ready nagari, a. The Importance of Forming a Disaster Response Team, Nagari Kataping needs to form a disaster response team consisting of the community, the Nagari government and related agencies such as BPBD b. Need to Prepare a Comprehensive Disaster Management Plan, Nagari Kataping must prepare a disaster management plan which includes risk identification, mitigation measures, evacuation plans, and resource allocation 2) Process of forming a disaster response nagari, Process of forming a disaster response alert Nagari in Nagari Kataping involving active participation of the community and related parties, focusing on coordination, education, training, procurement of equipment, formation of organizational structure, training and outreach 3) Effectiveness of Nagari Disaster Response Response, a. Public awareness, Nagari Siaga Disaster Response succeeded in creating public awareness of the importance of disaster preparedness and response through outreach and the formation of volunteer groups. b. Information and communication systems, disaster response villages have established an effective communication and coordination system between community groups, related agencies and BPBD so that when a disaster occurs the information will be conveyed more quickly and precisely.